The Use of Online Media in Migration Networks. Issue 6 (21st May 2015) - Dekker, Rianne; Engbersen, Godfried; Faber, Marije
Abstract: The use of online media for transnational communication in migration networks may serve as a new source of social ties and information for prospective migrants. There is scholarly debate about the role of online media communication in supporting migration aspirations and decision‐making. This paper aims to offer some context to this debate by studying to what extent online media are used for transnational communication in migrant networks and how personal characteristics, availability of social network ties, and migration propensity are influencing the likelihood of non‐migrants' use of online media. We draw on data of migrants in four Western European destination countries (the Netherlands, Norway, Portugal, and the UK) and non‐migrants in three origin countries (Brazil, Morocco, and Ukraine). Our results show that online media have indeed become fairly important channels of communication in migration networks. Online media use by non‐migrants is explained by age, level of education, and country of origin. Furthermore, the availability of migration network ties is relevant: Having more social ties leads to a higher likelihood of online media use. Online communication mostly takes place between existing social ties but may also concern establishing new 'latent' ties. Finally, we found that the use of online media to communicate with migrants in Western Europe is explained by the non‐migrants' migration propensity, indicating that online communication in migration networks is supporting migration aspirations and decision‐making. Copyright © 2015 John Wiley & Sons, Ltd.